Les petites stations thermales des Pyrénées centrales : des investissements privés au service d’une offre thermale de proximité - Géraldine Baglin (Les Cahiers de Framespa)
From the end of the 18th century and especially in the 19th century, the Pyrenees were a privileged area for the development of thermal baths. However, as in other territories, thermal activity did not develop homogeneously throughout the massif. The central part, for example, is characterised by a large number of small spas. The six sites mobilized in the study (Cadéac and Ferrère in the Hautes-Pyrénées, Couret and Ganties in Haute-Garonne, Audinac and Sentein in Ariège) show that the evolution of these resorts has been conditioned by multiple factors : economic, sociological, geographical, and political. The comparative analysis of the trajectories of these health resorts then makes it possible to identify the common features in the development of this type of resort.